Gut bacterial communities in roadkill animals: A pioneering study of two species in the Amazon region in Ecuador. - Manuel Alejandro Coba-Males; Magdalena Díaz; C Alfonso Molina; Pablo Medrano-Vizcaíno; David Brito-Zapata; Sarah Martin-Solano; Sofía Ocaña-Mayorga; Gabriel Alberto Carrillo-Bilbao; Wilmer Narváez; Jazzmín Arrivillaga-Henríquez; Manuela González-Suárez; Sandra Enríquez; et al. (PLoS ONE)
Studying the microbial communities within the gastrointestinal tract of vertebrate species can provide insights into biodiversity, disease ecology, and conservation. Currently, we have very limited understanding of the composition of endogenous microbiota in wildlife, particularly in high biodiversity tropical areas. Knowledge is limited by the logistical and ethical challenges of obtaining samples for free-living animals. Roadkill carcasses offer a largely untapped source for biological material, including endogenous gut microbiota. These animals that have died on roads due to collisions with vehicles are suitable for accessible, opportunistic sampling. Here, we used metabarcoding for the V3-V4 region of the 16S rRNA gene in gut samples of nine roadkill samples collected from a road in Ecuador representing two vertebrate species: the speckled worm lizard (Amphisbaena bassleri) and the smooth-billed ani (Crotophaga ani). We successfully identify microbial phyla in both samples including Firmicutes, Bacteroidetes, and Proteobacteria for A. bassleri, and Firmicutes and Actinobacteria for C. ani. Our study provides the first description of the gut microbiota for these two vertebrates, and demonstrates the feasibility of studying endogenous microbial communities from roadkill material that can be opportunistically collected and preserved in biobanks.